Proposed Product Requirement to Increase Adoption Rate of PT XYZ Campaign Management System - Fiemaelia Puterisantoso; Sudrajati Ratnaningtyas (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
The ever-increasing use of social media presents a huge opportunity for the marketing industry to leverage digital channels as a key strategy. PT XYZ, a company that focuses on data analysis, developed a Campaign Management System to help companies monitor marketing campaigns using internal influences such as employees. Despite its potential, the adoption rate of this system has not yet met the minimum expectations of customers. The research aims to identify the key needs of users and determine features that can increase adoption rates. This research method uses a qualitative approach with in-depth interviews with selected customers and internal document analysis. The data is analyzed to find patterns of user needs for relevant features. The results show that the adoption rate of the platform is closely related to features that increase user motivation, such as transparency of program information, integrated insight reports, and gamification. The addition of educational features and artificial intelligence-based content generators is also proposed to help influencers create creative content. In conclusion, increasing the adoption of Campaign Management Systems requires the development of features that are relevant to the needs of users, both from the admin and influencer sides. This research implies that PT XYZ can improve product competitiveness and sustainability in the industry through a platform that is more responsive to user needs